Protective Effect of Dictyophora rubrovolvata Extract on Intestinal and Liver Tissue Toxicity Induced by Metformin Disinfection Byproducts - Huijuan Liu; Dong Xiang; Jie Zhou; Jiao Xie (Toxics)
Metformin disinfection byproducts Y and C have emerged as pollutants of concern in drinking water systems and are suspected to possess significant toxicity to mammals. However, effective strategies to mitigate the effects of Y and C exposure in mammals have not been thoroughly formulated. This study aimed to investigate the toxicity and characteristic phenotypes of short-term, high-dose exposure to Y and C in the intestine and liver of mice and to evaluate the protective effects of Dictyophora rubrovolvata extract (DRE) on Y- and C-induced intestinal and liver damage. The results showed that exposure-induced intestinal toxicity manifested mainly as intestinal barrier dysfunction, induction of immune response and oxidative stress, and disruption of intestinal flora homeostasis. Hepatotoxicity was mainly characterized by histopathological changes such as vacuolar degeneration, abnormal liver function, and oxidative stress. Additionally, marked changes in gut microbiota and biochemical indicators were closely related to hepatic and intestinal injuries after exposure. DRE effectively alleviated Y- and C-induced intestinal and liver damage, reshaped the gut microbiota, and maintained gut–liver axis homeostasis. These findings provide new insights into the toxic effects of disinfection byproduct exposure through the gut-liver axis and suggest that functional food extracts may serve to protect against these adverse health outcomes.